Differences in pathogenicity and virulence-associated gene expression among Pasteurella multocida strains with high and low virulence in a lung tissue model. (March 2020) - Cheng, Yan; Wang, Kaicheng; Lin, Lishan; Zhao, Xingkai; Pan, Zihao; Zhou, Zhenlei
Abstract: Pasteurella multocida capsular type A can cause a pulmonary infection, leading to serious pecuniary losses in cattle. The heterogeneity of infection outcome of P. multocida strains showing different virulence may be related to divergent expression of virulence genes. In this study, we compared the transcriptional response of virulence-associated genes in high (PMPAN001) and low (PMPAN007) virulence P. multocida capsular type A strains in lung tissues and in vitro . These clinical isolates differ in their organ bacterial loads, mRNA abundance of the same virulence genes between lung and culture medium, and extent of lung damage. Among the eight virulence-associated genes ( fimA, tbpA, exbD, fur, oma87, pmHAS, nanH, and tonB ), seven genes showed higher expression in lung compared with in vitro at 16 h ( P ≤ 0.05) in PMPAN001, but not in PMPAN007. FimA, exbD, fur, oma87, pmHAS, and tonB gene transcripts showed significantly higher expression in PMPAN001 than in PMPAN007 in the lung tissues at 16 h post-infection ( P ≤ 0.05). Specially, the virulence gene, nanH, in both strains was associated with poor expression in vitro and lung tissue (mean relative mRNA abundance values < 0.6). Strain PMPAN001 had a higher proliferation rate in vivo than strain PMPAN007. The bacterial loads of PMPAN001 in the organs increased from 12 h post-infection, with maximum bacteria count ranging from 1 million to 20 million/mg. In addition, lungs treated with PMPAN001 produced serious and extensive lesions marked with inflammation at 20 h. Overall, our results reveal that the highly expressed virulence-associated genes, fimA, exbD, fur, oma87, pmHAS, and tonB can be used as markers for assessing the virulence of P. multocida capsular type A strains. Highlights: High-virulence P. multocida capsular type A strain had a higher proliferation rate in vivo than low-virulence strain, especially in lung tissues. There were significant differences in transcripts of virulence-associated genes between high and low-virulence strains in lung tissues. The level of virulence-associated genes transcripts in vitro did not agree with the in vivo situation in isolates.